Timberland transaction costs and due diligence: a literature review and assessment of research needs. (1st June 2020) - Hiegel, A.; Siry, J.; Bettinger, P.; Mei, B.
In the last three decades, purchases and sales of large timberland estates have become a common event worldwide. Timberland investments generally entail the purchase of land containing (or suitable for growing) merchantable timber in order to obtain future cash flows and an appreciation in the value of the entire estate. This review documents many of the critical steps involved in a comprehensive due diligence of investable timberland estates, and illustrates the sources and components of the transaction costs involved. Detailed insights into the processes involved in assessing potential timberland transactions and how market participants conduct these transactions are presented. These are followed by the discussion of implications of these findings for investment decisions and the assessment of pertinent research needs. This review attempts to create a framework to discuss and investigate the relevant costs of the due diligence process. Since almost no forestry due diligence literature was discovered, future research may then build upon this framework.